PROSELYTISM IN KYRGYZSTAN - MURZAKHALILOV, Kanatbek (CENTRAL ASIA AND THE CAUCASUS, 2004)
In independent Kyrgyzstan the rich and multisided spiritual life of its peoples, including religious confessions, is flourishing as never before. Having firmly resolved to build a democratic society our re-public was one of the first in the CIS to pass the most democratic law on the freedom of conscience. It has no rivals in legislations of both newly independent and developed democratic states.